The Effect of Autologous Dendritic Cell Immunotherapy on Kidney Function and Endothelial Dysfunction of Patients with Diabetic Kidney Disease (DKD): An Open Label Clinical Trial - Martina Lily Yana; Enda Cindylosa Sitepu; Jonny; Linda Chiuman; I Nyoman Ehrich Lister; Terawan Agus Putranto (Current Issues in Molecular Biology)
This study aimed to evaluate the effects of autologous dendritic cell (DC) immunotherapy on clinical outcomes (glomerular filtration rate/GFR and urine creatinine albumin ratio/UACR) and endothelial dysfunction (ICAM, VCAM, VEGF) in patients with diabetic kidney disease (DKD). Endothelial dysfunction induced by inflammation is one of the key factors in the pathogenesis of DKD. In this one-group pretest–posttest quasi-experimental study, 69 subjects with DKD were administered a single dose of autologous DC immunotherapy ex vivo. UACR was measured at baseline and at weeks 1, 2, 3, and 4, while ICAM, VCAM, VEGF, and GFR were measured at baseline and at week 4 post-immunotherapy. The results showed a significant reduction in median UACR from 250 (IQR 71–668) mg/g at baseline to 164 (IQR 49–576) mg/g at week 4 (p < 0.05). GFR did not show any significant changes after immunotherapy. HbA1c (B = −33.270, p = 0.021) and baseline UACR (B = −0.185, p < 0.001) were identified as significant predictors of UACR change. Although there were no significant changes in ICAM, VCAM, and VEGF, subgroup analysis revealed a decrease in VCAM in macroalbuminuria patients and an increase in those with good glycemic control, suggesting differing endothelial responses. In conclusion, autologous DC immunotherapy effectively reduced UACR in DKD patients, and significant VCAM changes were found in macroalbuminuria and good glycemic control subjects. Further research is needed to understand the mechanisms behind UACR reduction and the long-term impact of this therapy.